2022
DOI: 10.1098/rsob.220004
|View full text |Cite
|
Sign up to set email alerts
|

Notch signalling in healthy and diseased vasculature

Abstract: Notch signalling is an evolutionarily highly conserved signalling mechanism governing differentiation and regulating homeostasis in many tissues. In this review, we discuss recent advances in our understanding of the roles that Notch signalling plays in the vasculature. We describe how Notch signalling regulates different steps during the genesis and remodelling of blood vessels (vasculogenesis and angiogenesis), including critical roles in assigning arterial and venous identities to the emerging blood vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 156 publications
(190 reference statements)
0
25
0
Order By: Relevance
“…PDGFRβ knockout embryos lack pericytes and vSMCs and thus PDGFRβ expression is not specific to pericytes ( Noskovičová et al, 2014 ). PDGFRs are activated by the binding of ligands which triggers consequent cell signalling cascades that regulate cell proliferation, differentiation, migration, mural cell coating, and survival ( Thijssen et al, 2018 ; Del Gaudio et al, 2022 ).…”
Section: Pericyte Responses To the Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…PDGFRβ knockout embryos lack pericytes and vSMCs and thus PDGFRβ expression is not specific to pericytes ( Noskovičová et al, 2014 ). PDGFRs are activated by the binding of ligands which triggers consequent cell signalling cascades that regulate cell proliferation, differentiation, migration, mural cell coating, and survival ( Thijssen et al, 2018 ; Del Gaudio et al, 2022 ).…”
Section: Pericyte Responses To the Microenvironmentmentioning
confidence: 99%
“…The PDGF-B/PDGFRβ signalling axis serves as a paracrine endothelium-to-mural cells signalling loop which is initiated in the endothelium where the PDGF ligand is produced and secreted and receptor activation drives the differentiation of mesenchymal progenitor cells to mural cells and promotes mural cell coating of the blood vessels ( Gaengel et al, 2009 ; Del Gaudio et al, 2022 ). PDGF-B/PDGFRβ signalling mediates the recruitment of pericytes to the endothelial cells of new vessels thus providing support and secreting additional cytokines to aid in angiogenesis ( Thijssen et al, 2018 ).…”
Section: Pericyte Responses To the Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the need for further investigation of mechanisms related to Notch especially in the early stages of disease progression. These studies could include Notch associated mechanisms related to sprouting and splitting angiogenesis induced by ischaemia in the micro-environment [52,53]. One study exemplifying possible approaches investigated the angiogenic factor canopy 2 in a mouse pressure overload model and reported that expression of the factor produced beneficial effects in the progression from hypertrophy to dilated failure [54].…”
Section: Notch Signalling Ischaemia and Microvascular Dysfunction In ...mentioning
confidence: 99%
“…Notch signaling is key regulator of normal vascular development. The roles of Notch in normal vascular biology range from serving a critical role in the first phase of vascular development, i.e., vasculogenesis, during which loss of Notch signaling leads to an aberrant vascular bed and embryonic death in mouse models with perturbed Notch signaling; for review, see [ 138 ]. Notch signaling is furthermore important for establishing the arterial and venous sides of the endothelium, as well as for sprouting of the blood vessels during angiogenesis.…”
Section: The Role Of Notch Signaling In the Tumor Microenvironmentmentioning
confidence: 99%